واقع استخدام معايير الاعتماد الاكاديمي في العملية التعليمية دراسة تجريبية لعينة من كليات جامعة الكوفة - قاسم محمد العنزي; مريم ابراهيم الگرعاوي; حيدر جاسم الجبوري (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص استهدف البحث التعرّف على وقیاس امكانیة استخدام معاییر الاعتماد الاكادیمي لتحسین العملیة التعلیمیة في جامعة الكوفة. وتكون مجتمع البحث من التدریسیین في كلیات (الطب، طب الاسنان، الطب البیطري، القانون، الهندسة، الآداب، الریاضیات وعلوم الحاسبات، الادارة والاقتصاد، الفقه، التربیة، التربیة الاساسیة، التخطیط العم ا رني، الاثار والت ا رث)، أما عینة البحث فكانت مجتمع البحث البالغ ( 80 ) تدریسي من العمداء ومعاونیهم ورؤساء الاقسام العلمیة وتم استرجاع ( 48 ) استبانة صالحة وكانت نسبتها ( 60 %)، ووضع البحث ثمانیة فرضیات لبیان مدى تطبیق المعاییر في الكلیات عینة واهم ما توصل ألیه البحث .(SPSS) البحث. واستخرجت النتائج باستخدام الب ا رمج الإحصائیة الجاهزة بأنه الاساتذة في الكلیات عینة البحث قد اخذوا بنظر الاعتبار تلك المعاییر إلا أنها لم تكن بالمستوى المطلوب للبعض منها. ((The reality of the use of academic accreditation standards in the educational process)) experimental study of a sample of the faculties of the University of Kufa Abstract Aimed research to identify and measure the possibility of the use of academic accreditation standards to improve the educational process at the University of Kufa. As the research community of lecturers in colleges (medicine, dentistry, veterinary medicine, law, engineering, Arts, Mathematics and Computer Science, Administration and Economics, Fiqh, Education, Basic Education, Urban Planning, Antiquities and Heritage), the research sample was the research community (80) of deans and teaching assistants and heads of scientific departments have been retrieved (48) questionnaire was valid and percentage (60%), and the search mode eight hypotheses to show the extent of the application of standards in colleges, research sample. The exhumed results using statistical programs Ready (SPSS). The main conclusions of research that lecturers at colleges research sample may have taken into account those standards, but they were not at the required level for some of them